Deteksi dan Mitigasi Serangan Backdoor Menggunakan Python Watchdog - Susilo Hartono; Khusnul Khotimah; Hartono Hartono (LPPM Universitas Muhammadiyah Kotabumi, 2022)
The number of cyber attacks is increasing. This happens thoroughly, both at the international and national levels. Technology, techniques, and methods of carrying out cyber attacks are also increasingly sophisticated and up-to-date. Responding to this phenomenon, this research was conducted to implement an application for detecting and mitigating backdoor-based attacks using Python Watchdog. The method used in this study is the experimental method. This research is a case study of backdoor attacks that have been experienced by Universitas Muhammadiyah Kotabumi. In August – December 2021, one of the servers owned by Universitas Muhammadiyah Kotabumi received a significant backdoor-based attack. This research implements Python Watchdog to detect foreign files that are indicated as a backdoor, then sends notifications. Referring to the notification, the administrator can take further action. Based on the research that has been done, Python Watchdog is proven to overcome backdoor attacks. Once Python Watchdog is enabled, backdoor attacks are no longer possible.